THE CORRELATION OF FAMILY SUPPORT WITH THE LEVEL OF ANXIETY OF PRIMIGRAVIDA PREGNANT WOMEN IN FACING LABOR - NARESWARI NUGRAHA; CANDRA DEWI NATANINGTYAS (Indonesian Midwifery and Health Sciences Journal)
Introduction Anxiety in pregnant women is a common psychological condition where mothers feel anxious, restless, or worried about pregnancy, childbirth, or their future as a mother. This anxiety can be caused by various factors, including hormonal changes, physical changes that occur during pregnancy, uncertainty about the birthing process, feelings of not being ready to become parents, and concerns about the health of the baby and oneself. The purpose of this study is to examine the connection between primigravida pregnant women's anxiety levels and their amount of support from their families when it comes to giving birth. Method :This research design method uses a cross-sectional design. The population in this study was 75 third-trimester primigravida pregnant women. The total sample was 56 respondents using the purposive sampling technique. The sample was determined based on inclusion criteria, namely pregnant women who were willing to be respondents and pregnant women in the third trimester without complications. The analysis test used uses Spearman rho correlation. Result Analysis test results using Spearman rho correlation show a correlation value (r) = 0.716 with a p value of 0.000, where p < α (α = 0.05). This means that H1 is accepted and H0 is rejected. The results of this study can be concluded that family support is correlated with the level of anxiety of primigravida pregnant women. Based on this research, it is recommended that families can provide family support to primigravida pregnant women before delivery. Conclusion : the majority of primigravida pregnant women receive high family support and have mild levels of anxiety.